Biodiesel Production from Waste Cooking Oil Purified with Activated Charcoal of Salak Peel - Luqman Buchori; Dinda Labibah Ubay; Khonsa Syahidah (Dept. of Chemical Engineering, Diponegoro University, 2018)
Biodiesel is one of diesel fuel alternative made from renewable resources such as vegetable oils and animal fats. One of the natural ingredients that can be used as a material in the production of biodiesel is waste cooking oil (WCO). Biodiesel from WCO can be made through a transesterification reaction using a CaO catalyst. Free fatty acid (FFA) content in WCO needs to be reduced by activated charcoal adsorption. This research aims to determine the optimum time of adsorption by activated charcoal that made from salak peel and to determine the effect of transesterification temperature on biodiesel yield. The results showed that the FFA content of WCO decrease from 6.16% to 0.224% with adsorption time is 80 minutes and 10 gram of activated charcoal. Biodiesel yield increase by increasing transesterification temperature. The appropriate temperature is 50oC with 86.40% of yield, 887.2 kg/m3of density, 5.174 mm2/s of kinematic viscosity and acid number 0.421 mg KOH/gram sample. The composition of alkyl ester was obtained 65.54% with a FAAE yield of 56.63%.